СЕМАНТИЧЕСКОЕ МИКРОПОЛЕ СЛОВ С ОБЩИМ ЭТИМОНОМ ‘ПОЕДАЮЩИЙ / ПОЖИРАЮЩИЙ’ (Philological Studies, 2019)
This article examines the structure of etymology-semantic microfield formed by lexical units with native and borrowed basics -to eat and -phage [​